2017
DOI: 10.3846/13923730.2017.1343200
|View full text |Cite
|
Sign up to set email alerts
|

Suggesting a Simple Design Method for Cold Recycled Asphalt Mixes With Asphalt Emulsion

Abstract: Although there are typical and well-known standard methods for designing hot mix asphalt in the world, there is no unique design method for cold recycled asphalt mixes. The current methods are mainly local or even dependent on technology owners due to the diversity of materials and qualitative control limitations. Currently, most of the design methods are based on 4 inch mold. The major problem of these methods is that in the mix design, the effect of aggre­gates larger than 25 mm is neglected, while this size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…An important issue concerning FA-stabilized materials is the absence of a mix design methodology suitable for CIR mixes [16]. Some researchers have pinpointed the moisture susceptibility of Foamed Asphalt base materials [17], especially prior to Asphalt Concrete (AC) overlay construction [18], while others have concluded that FA outperforms bitumen emulsion for base stabilization in terms of increased moisture and frost resistance [8,18].…”
Section: Introductionmentioning
confidence: 99%
“…An important issue concerning FA-stabilized materials is the absence of a mix design methodology suitable for CIR mixes [16]. Some researchers have pinpointed the moisture susceptibility of Foamed Asphalt base materials [17], especially prior to Asphalt Concrete (AC) overlay construction [18], while others have concluded that FA outperforms bitumen emulsion for base stabilization in terms of increased moisture and frost resistance [8,18].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, much research has focused on improving the properties of cement-emulsified asphalt mortar and mixtures [ 4 , 5 , 6 ]. Specifically, mechanical properties, including indirect tensile strength (ITS), indirect tensile stiffness modulus, creep stiffness, and durability in term of water sensitivity of cement-emulsified asphalt mixture have been investigated [ 7 , 8 , 9 , 10 ]. Meanwhile, road performance, such as wheel-tracking and fatigue performance, have also been studied [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al (2003) believed that the Marshall compaction method could not simulate the compaction effect of the field road compaction machinery, and proposed to use the gyratory compactor to compact and form a cold recycled mixture. Moghadam and Mollashahi (2017) thought that when the particle size was larger than 25 mm, a significant difference in the mechanical properties and water stability was found between the 4-inch and 6-inch specimens. Guo compared the Marshall compaction test with the gyratory compaction test and showed that the voids of the Marshall compaction specimen were basically the same as that of 40 50 times of gyratory compaction specimen (Guo, 2013).…”
Section: Introductionmentioning
confidence: 99%